Desenvolvimento de sistema para monitoramento e controle de biorreator airlift de escala de bancada - Torresam, Gabriel Deriggi (2013)
In the present work it was developed a system for monitoring and control of a bench scale concentric-tube airlift bioreactor of 5.0 L working volume. The software-based language G (Labview) provides the user monitor important process variables such as dissolved oxygen concentration, pH, volumetric flow rate of feed, pressure difference between two points along the axial direction and temperature in two regions of liquid phase flow phase, and it can act in the volumetric flow rate and gas stream composition at the input of bioreactor. Overall gas hold-up (eG) and gas hold-up in riser (eR) and downcomer (eD) regions were determined using volumetric expansion and gauge measurement methods. Mixing time (tm) and circulation time (tC) were determined by thermal and pH pulse methods. Dynamic pressure method was utilized for evaluating mass transfer measurement in airwater biphasic system. These methods were utilized in order to obtain significant hydrodynamic performance parameters as a function of superficial gas velocity in the riser (UGR). Analyses of the oxygen transfer dynamics were also used in the development of automatic control loop to control the dissolved oxygen concentration. As a concrete result, this study provided software for data acquisition and monitoring of all sensors in pneumatic bioreactor, providing a tool to explore the hydrodynamic performance and control of the dissolved oxygen concentration in concentric-tube airlift bioreactor during aerobic cultivations. The system validation was performed by comparing the results obtained in the hydrodynamics tests with those of literature and control loop was tested in simulations involving a cultivation of a strictly aerobic microorganism.